Propaganda in the North Korea Cartoons: Discursive and Subtext Analysis in Animated Series and Short Films of North Korean Production - Naudín Escuder, Eduardo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
Through the analysis of some short films and series of government propaganda produced in North Korea since the 80s to the present, this work intends to explore the way in which the government of Kim Jong Un relates to the mass media, and on the other hand, to unravel those discursive mechanisms of the audiovisual text that pretend to alter the consciences of the youngest. In addition, a reflection is opened, which is latent throughout the practical investigation, about how violence is presented on screen and its possible effects among the youngest.